Towards closing the attitude-intention-behavior gap in green consumption: A narrative review of the literature and an overview of future research directions - ElHaffar, Ghina; Durif, Fabien; Dubé, Laurette (Journal of cleaner production, 2020)
Research on sustainable consumption has gained much popularity in the past few years, and the of the green gap phenomenon has had its share of studies. This phenomenon is known as the discrepancy between what consumers say about their growing concern regarding the environment, on the one hand, and what they truly do to help sustain this environment, on the other hand. Although reviews of the motivations and barriers of green consumption are available in the literature, none of them focuses on the green gap, nor examines the methodologies and paradigms used in the available studies. Given the importance of methodology in creating the green gap, and considering the effect of the adopted paradigm on the reliability of the results, it is essential to identify these two aspects in each reviewed study. In this work, we use a pre-assigned framework to categorize 58 articles addressing the green gap, based on the theory, methodology, and paradigm applied in each article. An overview of the studies shows that despite the diversity of methods used, there is still room for improvement in terms of methodology, paradigm, and theory. Most importantly, qualitative studies and experimental designs are needed, and the rational paradigm must not be replaced by but should instead complement the current trend that favors the behavioral economic. As for the theoretical improvements, the research focus must shift from exploring the reasons behind the gap to implementing solutions to it. •Research on the green attitude-behavior gap is reviewed, analyzed and summarized in a comprehensive framework.•This literature review focuses on theories, methodologies, and paradigms in past research on the green gap.•Considering the methodological along with the modeling variables will potentially limit the gap and produce more reliable results.•Solutions to the gap must not be limited to behavioral interventions.•Solutions should cover interventions rooted in the traditional rational paradigm such as self-cognition and self-awareness.•Aligning the paradigm with the type of consumers targeted is essential.•Consumer segmentation based on the green gap could help design more effective interventions.